2022
DOI: 10.2196/30113
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Aloud or Screaming Inside: Exploratory Study of Sentiment Around Work

Abstract: Background Millions of workers experience work-related ill health every year. The loss of working days often accounts for poor well-being because of discomfort and stress caused by the workplace. The ongoing pandemic and postpandemic shift in socioeconomic and work culture can continue to contribute to adverse work-related sentiments. Critically investigating state-of-the-art technologies, this study identifies the research gaps in recognizing workers’ need for well-being support, and we aspire to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…There is proof that being exposed to weather hazards has a negative influence on people's physical and mental health, especially in places affected by heat islands and climate change. The study in [71] reveals how Twitter data may be used to measure urban heat stress in real time and serve as a quick signal of times when people are feeling more uncomfortable due to the heat and are more likely to be dissatisfied with the weather.…”
Section: B the Relevant Sectors Of Activity Where The Clustering Algo...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is proof that being exposed to weather hazards has a negative influence on people's physical and mental health, especially in places affected by heat islands and climate change. The study in [71] reveals how Twitter data may be used to measure urban heat stress in real time and serve as a quick signal of times when people are feeling more uncomfortable due to the heat and are more likely to be dissatisfied with the weather.…”
Section: B the Relevant Sectors Of Activity Where The Clustering Algo...mentioning
confidence: 99%
“…Moreover, the inhabitants of a region may presently convey their own experiences with warm weather as well as their sentiments about it on SM. The public mood and health of an area may be reflected in the geotagged, time-stamped, and easily available SM databases, according to a recent study published by [71]. Further, research on the emotional data may be done using the Roulette wheel selection based cuckoo search clustering method [19].…”
Section: ) Society and Political Views (Elections)mentioning
confidence: 99%
“…There have been several reports of NLP studies targeting workers. For example, a study investigating work-related tweets using Twitter reported that tweets containing words such as “life” and “need” were included regardless of the emotion expressed in the tweet [ 25 ]. Another study that used NLP to investigate work-related suicides in the National Violent Death Reporting System database identified factors such as mental health issues and conflicts in relationships as preceding factors of suicide [ 26 ].…”
Section: Introductionmentioning
confidence: 99%